Early diagnosis of junior school age children’s posture disorders - Razumeiko, N.S. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: to describe specificities of early diagnosis method for junior school age children’s posture disorders. Material: in pedagogic experiment 156 junior school age children (boys and girls of 7-10 years’ age) participated. All children had no experience of training in sport circles. For determination of uniformity of the tested we fulfilled experts’ examination for presence or absence of external signs of posture disorders in frontal plane. The children’s examination was conducted by qualified specialists at the beginning and at the end of experiment. For determination of early signs of muscular asymmetry in torso right and left sides of the tested children we used methodic, based on registration of tonic vibration reflex. Results: the pupils’ examination permitted to form a group of 108 persons, who did not have external signs of posture disorders. It was proved that it would be purposeful to take prophylaxis measures at very early stages of imbalance in muscular system’s work. Traditional approach in the form of prophylaxis examination can not give confident information about initial stage of imbalance in muscular system’s work in child’s organism. Conclusions: it was found that imbalance of motor nervous centers reflex excitability on both sides of backbone (if no purposeful prophylaxis measures are taken) can result in muscular tonus asymmetry on right and left sides of torso in lumbar spine area.